Pengaruh Net Profit Margin dan Total Asset Turnover Terhadap Pertumbuhan Laba Pada Perusahaan Makanan Dan Minuman yang Terdaftar di BEI Tahun 2019-2022 - Dwi Z, Aghnia; Suherman, Acep; Sofiani, Venita (Magister Ilmu Akuntansi Universitas Jambi, 2024)
This study aims to determine the effect of net profit margin and total asset turnover on profit growth. The variables used in this study are net profit margin, total asset turnover and profit growth. The research method used in this study is a quantitative method with descriptive research type, sampling in this study was carried out by purposive sampling method with predetermined criteria resulting in 19 companies. The analytical method used is multiple linear regression analysis with SPSS version 25. The partial results show that Net Profit Margin (NPM) has an effect on profit growth while Total Asset Turnover (TATO) has no effect on profit growth. The simultaneous results show that the net profit margin and total asset turnover have a simultaneous or equal effect on profit growth.